Dynamic response analysis of a floating vertical axis wind turbine with helical blades based on the model test. (1st April 2023) - Deng, Wanru; Guo, Ying; Liu, Liqin; Li, Yan; Jiang, Yichen; Xie, Peng
Abstract: The helical type floating wind turbine can be a promising choice to harvest offshore wind energy because it has the merits of straight blade floating VAWTs and could reduce the aerodynamic torque fluctuations. In this study, the wave basin model tests for a 5 MW helical type floating wind turbine were carried out, and the dynamic response behaviors are specifically discussed. In general, the motions of the floating foundation obey the regularity that aerodynamic loads mainly affect the average value while hydrodynamic loads affect the standard deviation. For the mooring system, the tensile forces are dominated by the floating foundation motions as well as the stiffness behavior of the mooring lines. Furthermore, the comparative study is conducted with the numerical results of a floating HAWT. It is found that the standard deviations of heave and pitch motions of the helical type floating wind turbine are slightly smaller than those of floating HAWT, while the standard deviations of surge and yaw motions are larger. As to the mooring system, the tensile force of mooring line 1 of helical type floating wind turbine is smaller than that of floating HAWT, while the tensile forces of mooring lines 2 and 3 are larger. Highlights: A 5 MW helical type floating VAWT was experimentally modeled and tested. Dynamic responses of the helical type floating VAWT are investigated under various experimental cases. Dynamic responses of the helical type floating VAWT are compared with numerical results of the floating HAWT.